STRATEGI MENINGKATKAN KETAHANAN PANGAN DI DESA SARIREJO NATAR MELALUI OPTIMALISASI VERTICAL GARDEN DAN PERTANIAN ORGANIK PADA LAHAN TERBATAS - Yosi Dwi Saputra (LPPM Institut Pendidikan Nusantara Global, 2026)
Indonesia's food security faces challenges due to limited land availability resulting from the conversion of agricultural land into residential areas. Vertical Gardens and organic farming based on Liquid Organic Fertilizer (LOF) from household waste have emerged as innovative solutions to optimize limited land in rural areas. This community service program aims to integrate Vertical Gardens, organic farming, and LOF to enhance village food security in a productive, economical, and sustainable manner. The activity was conducted in Dusun IV Sarirejo, Natar District, South Lampung, using a participatory approach through lectures, discussions, and hands-on practice. The evaluation method employed pre-test and post-test assessments of 70 participants to measure improvements in understanding and skills. Pre-test results indicated that 80% of participants knew about organic waste as fertilizer, but only 10% utilized it and understood LOF production techniques and Vertical Garden implementation. Following the extension program, a significant increase of 88% was observed, with 98% of participants able to produce LOF from vegetable waste and apply Vertical Gardens in limited spaces. The participatory method based on hands-on practice proved effective in transferring knowledge and skills, creating opportunities for food diversification and household economic improvement. Program sustainability requires continuous mentoring, formation of Vertical Garden farmer groups, and integration with village development programs based on organic farming.